2020
DOI: 10.9770/jesi.2020.8.1(2)
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development and urban planning regulations in the context of climate change management measures

Abstract: The purpose of this paper is to evaluate recent and upcoming changes in urban planning legislation in the Republic of Lithuania, which acknowledge the necessity of introducing climate change management tools. Sustainable development is a core principle of the Spatial Planning Law of the Republic of Lithuania since 2014. Special attention to the management of climate change is given at the national and municipal levels, and recent legislative initiatives are proof of this. Methodologythis analysis is based on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Higher levels of government environmental governance can promote green total factor productivity in regional industries, but there is regional heterogeneity in the green eco-efficiency of environmental governance or environmental regulation (Wang and Sheng, 2015), while other scholars have examined the effect of environmental regulation on economic growth under environmental constraints. Klimas, E. (2020) analyzed the impact of spatial planning regulations on climate change management using the latest sustainable development principles in Lithuania and found that spatial planning regulations should provide for specific measures to effectively enhance climate management.An empirical study of the pilot policy's impact on civilized cities discovered that environmental regulation by the government can lower pollution levels and encourage the growth of green urban areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Higher levels of government environmental governance can promote green total factor productivity in regional industries, but there is regional heterogeneity in the green eco-efficiency of environmental governance or environmental regulation (Wang and Sheng, 2015), while other scholars have examined the effect of environmental regulation on economic growth under environmental constraints. Klimas, E. (2020) analyzed the impact of spatial planning regulations on climate change management using the latest sustainable development principles in Lithuania and found that spatial planning regulations should provide for specific measures to effectively enhance climate management.An empirical study of the pilot policy's impact on civilized cities discovered that environmental regulation by the government can lower pollution levels and encourage the growth of green urban areas.…”
Section: Literature Reviewmentioning
confidence: 99%